Ignition thresholds and flame propagation of methane-air mixture: detailed kinetic study coupled with electrical measurements of the nanosecond repetitively pulsed plasma discharges. (4th August 2022) - Mehdi, Ghazanfar; Fontanarosa, Donato; Bonuso, Sara; De Giorgi, Maria Grazia
Abstract: This study investigated the effects of nanopulsed plasma discharge on combustion enhancement. A disk-ring plasma actuator was developed to be applied to a rectangular cross-sectional burner. Experiments tests were performed with different applied voltages to estimate reduced electric field ( E N ), mean power and the energy input ( E i ) to be coupled with numerical analysis. The validation of the plasma chemistry model was carried out using ZDPlaskin numerical solver by comparing the experimental data of mole fraction of O atoms available in the literature. Plasma chemistry computations based on an extended kinetic mechanism of methane/air mixtures were performed by ZDPlasKin. Then, the results obtained by the ZDPlasKin in the form of kinetic effects (concentrations of O, OH, O3, CH, CH3, and H) and thermal effects (joule heating) were used in CHEMKIN to evaluate the combustion enhancement. Flame speed considerably increased with plasma discharge and maximum enhancement has been observed at about 20.9%. The flame temperature corresponding to the peak of heat release rate gets lower with the increase of the E i value. It has been observed that in a clean case, a lower flammability limit was retrieved at φ = 0.6, but in presence of plasma, it was reduced to φ = 0.5. The plasma actuation significantly reduced the time necessary to reach the ignition temperature with respect to autoignition (clean case). The maximum reduction of ignition delay timing was noticed at E i = 10.11 mJ cm −3 and E N = 200 Td, with a value between 10 −8 and 10 −7 s, significantly lower than the autoignition case is between 10 −3 and 10 −2 s. Adding to this, ignition analysis was also performed at low inlet temperatures. Results demonstrated that it was possible to reach ignition of CH4 /air mixture at a lower inlet temperature than the one required for self-ignition (without plasma), meaning that ignition is even possible in cold flow conditions using plasma. Finally, thermal and kinetic effects of plasma discharge on the ignition enhancement of methane–air mixture have been predicted. It concluded the ignition improvement is mainly due to O, H, and OH species, while the thermal effect was negligible.